Maquiavelismo: concepto y significado. Una lectura desde la virtù (2009)
Machiavellism or “machiavellian” are concepts used often as synonyms of immorality or of subordination of means to an end (a kind of embryonic utilitarianism). A more profound reading of The Prince, together with the analysis of the other works by Mac hiavavelli, reveals that the Florentine political writer was far from that thought. Works like those ones by Pocock and Lefort’s provide for an interesting rereading, from which it can be deduced that “Machiavellism” or “machiavellian” are not moral doctrines, but a way (amoral) of understanding power–more specifically, real relations of power. Here, the notion of virtù plays an essential role, since it involves the way in which Mac hiavavelli understands power and politics, being also the reason of the ambiguous interpretations towards the Florentine writer. Every ruler must be virtuous in a classic and in a machiavellian way. The ruler who is virtuous only in a machiavellian sense will be immoral, and the one who is virtuous only in a classical sense is or will be irresponsible.